The Aggregation Problem: Implications for Ecological and Biophysical Economics - Blair Fix (BioPhysical Economics and Resource Quality, 2019)
This article discusses the aggregation problem and its implications for ecological economics. The aggregation problem consists of a simple dilemma: when adding heterogeneous phenomena together, the observer must choose the unit of analysis. The dilemma is that this choice affects the resulting measurement. This means that aggregate measurements are dependent on one's goals, and on the underlying theory. Using simple examples, this article shows how the aggregation problem complicates tasks such as calculating indexes of aggregate quantity, and how it undermines attempts to find a singular metric for complex issues such as sustainability. [Data and analysis for this paper are available at the Open Science Framework: https://osf.io/3smra/]
Keywords: P16; P48; E01; C43; Q56; Q01; 330; aggregation; capital stock; GDP; natural capital; sustainability indices